Hematological Changes During All trimesters in Normal Pregnancy - Babker, Asaad Ma.; Elnaim, Elkhansa Osama Di (Journal of Drug Delivery and Therapeutics, 2020)
Aim: The objective of the study is to evaluate the normal physiological changes in values of major hematological parameters occur during the normal pregnancyMethod: Blood samples (5ml EDTA) were taken voluntarily after consent obtained from from 50 healthy pregnant women from 20 to 40 years old who presented themselves at Khartoum teaching during their regularly follow-up. Questionnaires and direct interview were used to collect demographic and clinical data. CBC and part differential (WBC, RBC, Hb, PCV, and platelets), were measured by Sysmex and the plasma clotting time PT and PTT were measured by coagulometer.Results: W'BCs mean value was 7.580 cell/mm3, RBCs mean value was 4.1 x l012/L, Hb mean value was 11.79 g/dL, Platelets mean value was 256 x109/L, PT mean value of the study group was 13.40 seconds and PTT mean value was 36.20 seconds.Conclusion: It can be concluded that no statistical significance in RBCs, HB, platelets. PT and PTT between pregnant women in the three different trimesters while white WBCs count showed different decreased but not statistical significant  among the three groups, the highest value was round in the second group followed by the third group and the lowest value found in the first group.Keywords: Normal pregnancy, Hematological Changes, Pregnancy trimesters